Identifikasi Perubahan Luas Lahan Perkebunan Kelapa Di Kecamatan Sungai Kakap Kabupaten Kubu Raya - Agus Ruliyansyah; Henny Sulistyowati (Fakultas Pertanian Universitas Tanjungpura, 2021)
Identification of Coconut Plantation Area Changes In Sungai Kakap Sub-District Kubu Raya Regency, Land cover turnover and land use cannot be averted. Growth of the city and change in needs of facilities have caused the agricultural and plantation lands to undergo change in their functions. This reasearch aims to identify the change of coconut plantation land area in Sungai Kakap sub-district, Kubu Raya regency. The methods used in this research were surveys and landsat imagery interpretation of 2002 and 2017. The result shows that there were an increasement of coconut plantation area amounted to 6452,19 ha or about 403 ha per year from 2002 to 2017. The increasement of plantation area is due to the improvement of coconuts' selling price, thus encouraging farmers to manage and to expand the plantation area of coconut.